2000
DOI: 10.1083/jcb.150.6.1489
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Regulates the Association between Mitochondria and a Smooth Subdomain of the Endoplasmic Reticulum

Abstract: Association between the ER and mitochondria has long been observed, and the formation of close contacts between ER and mitochondria is necessary for the ER-mediated sequestration of cytosolic calcium by mitochondria. Autocrine motility factor receptor (AMF-R) is a marker for a smooth subdomain of the ER, shown here by confocal microscopy to be distinct from, yet closely associated with the calnexin- or calreticulin-labeled ER. By EM, smooth ER AMF-R tubules exhibit direct interactions with mitochondria, identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(125 citation statements)
references
References 35 publications
7
115
0
2
Order By: Relevance
“…AMF/PGI affect on [Ca 2 þ ] cyt elevation was not however affected by mitochondrial uncoupling, suggesting that it is not related to mitochondrial association of the gp78/AMFRlabeled smooth ER domain. 24,32 It was also not associated with changes in ER Ca 2 þ content. AMF/PGI interaction with gp78/AMFR, therefore, regulates ER Ca 2 þ release upon ER stress.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…AMF/PGI affect on [Ca 2 þ ] cyt elevation was not however affected by mitochondrial uncoupling, suggesting that it is not related to mitochondrial association of the gp78/AMFRlabeled smooth ER domain. 24,32 It was also not associated with changes in ER Ca 2 þ content. AMF/PGI interaction with gp78/AMFR, therefore, regulates ER Ca 2 þ release upon ER stress.…”
Section: Discussionmentioning
confidence: 82%
“…11 The gp78/AMFRpositive smooth ER domain is closely associated with mitochondria and this interaction is regulated by [Ca 2 þ ] cyt . 24,32 In response to TG and TUN, AMF/PGI reduced the peak amplitude although not total (AUC) elevation of [Ca 2 þ ] cyt and importantly affected the rate of Ca 2 þ uptake to mitochondria. AMF/PGI affect on [Ca 2 þ ] cyt elevation was not however affected by mitochondrial uncoupling, suggesting that it is not related to mitochondrial association of the gp78/AMFRlabeled smooth ER domain.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2 þ also regulates the association between mitochondria and a smooth domain of the ER and enhances the ability of gangliosides to produce membrane clusters. 89 Whether mitochondrial damage occurs through ganglioside interaction with a candidate component of the PTP or through direct perturbation of mitochondrial membranes and, in turn, PTP function, remains to be elucidated. However, the fact that GD3-mediated opening of PTPs is antagonized by known PT inhibitors (e.g., cyclosporin A, ADP, trifluoperazine, and Mg 2 þ ) suggests that GD3 acts directly at the pore level.…”
Section: Gangliosides As Propagators Of the Er Stress-and Mitochondrimentioning
confidence: 99%
“…What is very interesting, however, is that both the SSC and mitochondria are most certainly dynamic structures, unlike their static images captured in electron microscopy. Early ultrastructural studies have demonstrated that SSCs are capable of plastic changes after axotomy and during development (Sumner, 1975;Buschmann, 1979), and recent evidence indicates that local Ca 2ϩ dynamics may affect physical coupling between the smooth endoplasmic reticulum and mitochondria (Wang et al, 2000). Finally, we should consider the possibility of a dynamic trafficking between the plasmalemmal component and the cytoplasmic pool of the D 5 R, as might indicate its selective clustering bellow the microdomain, often in association with clathrincoated vesicles (Fig.…”
Section: )mentioning
confidence: 99%